Internship, Employability and Organisational Commitment in the Hospitality Industry in Bauchi Metropolis, Bauchi State, Nigeria - Adelaiye, Mary B. O. (Àgídìgbo: ABUAD Journal of the Humanities, 2019)
This study investigates the relationship between internship and employability in the hospitality industry in Bauchi State. The study adopted the cross-sectional survey in its investigation of the variables. Primary source of data was generated through self- administered questionnaire. The population of the study consist of 81 respondents made up of management staff, human resource managers, internship supervisors as well as interns themselves drawn from two purposefully selected hotels (Larema Hotels & Suites and Command Guest House) in Bauchi metropolis. The sample size of 72 was determined using the Krejcie and Morgan table. After data cleaning, only data of 67 respondents were finally used for data analysis. Data generated were analysed and presented using both descriptive and inferential statistical techniques. The hypotheses were tested using the Spearman’s Rank Order Correlation Statistics. The findings revealed a positive but weak relationship between internship and employability in the hospitality industry in Bauchi metropolis, Bauchi State. The study recommended that organization should truly see internship as a recruitment process and commit resources to it which enable them to initiate requests for interns in desired areas of interests. This will lead to greater commitment from hosting organizations. The task of looking for internship placement should not be entirely left to the students.